Benefit and harm of adding ketamine to an opioid in a patient-controlled analgesia device for the control of postoperative pain: systematic review and meta-analyses of randomized controlled trials with trial sequential analyses. Issue 12 (December 2016) - Assouline, Benjamin; Tramèr, Martin R; Kreienbühl, Lukas; Elia, Nadia
Abstract : Abstract: Ketamine is often added to opioids in patient-controlled analgesia devices. We tested whether in surgical patients, ketamine added to an opioid patient–controlled analgesia decreased pain intensity by ≥25%, cumulative opioid consumption by ≥30%, the risk of postoperative nausea and vomiting by ≥30%, the risk of respiratory adverse effects by ≥50%, and increased the risk of hallucination not more than 2-fold. In addition, we searched for evidence of dose-responsiveness. Nineteen randomized trials (1349 adults, 104 children) testing different ketamine regimens added to various opioids were identified through searches in databases and bibliographies (to 04.2016). In 9 trials (595 patients), pain intensity at rest at 24 hours was decreased by 32% with ketamine (weighted mean difference −1.1 cm on the 0-10 cm visual analog scale [98% CI, −1.8 to −0.39], P < 0.001). In 7 trials (495 patients), cumulative 24 hours morphine consumption was decreased by 28% with ketamine (weighted mean difference −12.9 mg [−22.4 to −3.35], P = 0.002). In 7 trials (435 patients), the incidence of postoperative nausea and vomiting was decreased by 44% with ketamine (risk ratio 0.56 [0.40 to 0.78], P < 0.001). There was no evidence of a difference in the incidence of respiratory adverse events (9 trials, 871 patients; risk ratio 0.31 [0.06 to 1.51], P = 0.08) or hallucination (7 trials, 690 patients; odds ratio 1.16 [0.47 to 2.79], P = 0.70). Trial sequential analyses confirmed the significant benefit of ketamine on pain intensity, cumulative morphine consumption, and postoperative nausea and vomiting and its inability to double the risk of hallucination. The available data did not allow us to make a conclusion on respiratory adverse events or to establish dose-responsiveness. Abstract : Supplemental Digital Content is Available in the Text.